2021
DOI: 10.33418/ataunikkefd.796531
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenleri̇n Ters Yüz Öğrenme Öz-Yeterli̇k Algilari İle Öğrenen Özerkli̇ği̇ni̇ Destekleme Davranişlari Arasindaki̇ İli̇şki̇

Abstract: Bu araştırmada, öğretmenlerin ters yüz öğrenme öz-yeterlik algıları ve öğrenen özerkliğini destekleme davranışları arasındaki ilişkinin incelenmesi amaçlanmaktadır. İlişkisel tarama modelinin kullanıldığı bu araştırmanın çalışma grubu, 301 öğretmenden oluşmaktadır. Araştırmada "Öğrenen Özerkliğini Destekleme Ölçeği" ve "Ters Yüz Öğrenme Öğretmen Öz-Yeterlik Algı Ölçeği" kullanılmıştır. Veriler betimsel istatistikler, fark analizleri, Pearson Çarpım Momentler Korelasyon katsayısı ve basamaklı Kozikoğlu, İ. Erbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…In this study, it was determined that the acceptance levels of flipped mathematics classrooms differed statistically significantly in favor of those who considered themselves more sufficient in terms of their perception of ability in learning mathematics alone at home. On the other hand, the flipped classroom structure is seen to be associated with student autonomy as it requires students' active participation in learning (Chen et al, 2014;Han, 2015;Jenkins et al, 2017;Kozikoğlu et al, 2021). Supporting this situation, the study found a moderate and statistically significant relationship between secondary school students' autonomous learning scores and flipped mathematics classroom acceptance scores.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In this study, it was determined that the acceptance levels of flipped mathematics classrooms differed statistically significantly in favor of those who considered themselves more sufficient in terms of their perception of ability in learning mathematics alone at home. On the other hand, the flipped classroom structure is seen to be associated with student autonomy as it requires students' active participation in learning (Chen et al, 2014;Han, 2015;Jenkins et al, 2017;Kozikoğlu et al, 2021). Supporting this situation, the study found a moderate and statistically significant relationship between secondary school students' autonomous learning scores and flipped mathematics classroom acceptance scores.…”
Section: Discussionmentioning
confidence: 76%
“…In the flipped learning model, students have important learning responsibilities, especially in out-of-school learning (Kozikoğlu et al, 2021). In this study, it was determined that the acceptance levels of flipped mathematics classrooms differed statistically significantly in favor of those who considered themselves more sufficient in terms of their perception of ability in learning mathematics alone at home.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations